Upaya Meningkatkan Kemampuan Membaca Siswa Dengan Metode TGT (Teames Games Tournament) Pada Siswa Kelas IVA SDN 01 Mamben Daya Semester 1 Tahun Pelajaran 2021/2022 - Yanti, Ika Tija; Sopian, Asri (khatulistiwa, 2022)
This study aims to improve students' reading skills through the TGT (Teams Games Tournament) method. This type of research is CAR (Classroom Action Research) which is carried out in two cycles with each cycle being carried out in two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection which is carried out for two hours of lessons. The subjects of this study were students of class IVA SDN 01 Mamben Daya. Data collection techniques using observation, documentation and oral tests. The data analysis technique used is descriptive qualitative and descriptive quantitative. The results in the initial condition of students' ability to read words through the TGT (Teams Games Tournament) method only reached 11 students with a percentage of 50% belonging to the "completed" category while 11 students with a percentage of 50% belonging to the "incomplete" category. In the first cycle the increase in students' abilities increased by 13 students with a percentage of 63% belonging to the "completed" category while 9 students with a percentage of 37% belonging to the "incomplete" category. While in the second cycle there were 20 students with a percentage of 80% belonging to the "completed" category while 2 students with a percentage of 20% belonging to the "incomplete" category. So that research using the TGT (Teams Games Tournament) method is said to be successful in improving students' reading skills